2009
DOI: 10.1534/genetics.108.098475
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Receptor-Tyrosine-Kinase-Signaling Target Genes Reveals Receptor-Specific Activities and Pathway Branchpoints During Drosophila Development

Abstract: Receptor tyrosine kinases (RTKs) are an important family of signaling molecules with the unusual property that they are able to transduce their signals using the same downstream pathways. This has led to an unresolved debate as to whether individual receptors are interchangeable, or if each receptor can mediate specific downstream responses. To address this question, we have conducted a screen to identify target genes whose expression is differentially modulated by RTKs and their downstream pathway components.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 46 publications
2
9
0
Order By: Relevance
“…Expression of the FC markers org-1, kirre (also known as dumbfounded (duf )), and RhoGAP15B all appear normal in a pnt act background, whereas, as reported previously, expression of all three expands with pan-mesodermal expression of activated Ras (Ras act ) (Fig. 3; Leatherbarrow and Halfon, 2009, Lee et al, 2003). Doublelabeling with antibodies to Biniou, a general visceral mesoderm marker (Zaffran et al, 2001), showed that the observed expansion is throughout the visceral mesoderm (Fig.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…Expression of the FC markers org-1, kirre (also known as dumbfounded (duf )), and RhoGAP15B all appear normal in a pnt act background, whereas, as reported previously, expression of all three expands with pan-mesodermal expression of activated Ras (Ras act ) (Fig. 3; Leatherbarrow and Halfon, 2009, Lee et al, 2003). Doublelabeling with antibodies to Biniou, a general visceral mesoderm marker (Zaffran et al, 2001), showed that the observed expansion is throughout the visceral mesoderm (Fig.…”
Section: Resultssupporting
confidence: 76%
“…4C, D), responds to Ras act and Pnt act ectopic expression in the same manner (Fig. S1E, F and Leatherbarrow and Halfon, 2009), and shows a similar Ras act -like expansion of reporter gene expression when the remaining six ETS-type sequences are mutated (construct “mib2_FC626 ETS ; Fig. 4E, F, G).…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Although RTKs generally stimulate a similar complement of intracellular pathways, distinct features underlying the action of those pathways can lead to differential cellular responses (Kratchmarova et al, 2005;Leatherbarrow and Halfon, 2009;Lemmon and Schlessinger, 2010;Zand et al, 2011). In particular, quantitative changes in the strength or duration of RTK signaling can give rise to diverse cellular outputs (Marshall, 1995;Greenwood and Struhl, 1997;Lemmon and Schlessinger, 2010).…”
Section: Intrinsic Differences Between Signaling Networkmentioning
confidence: 99%
“…In a previous screen for genes that respond differentially to different Ras pathway components, we observed that, despite responding to RTK and Ras activation, the FC gene mib2 is not regulated by the Ras effector Pnt in the visceral mesoderm (Leatherbarrow and Halfon, 2009). Expression of both mib2 RNA and a mib2-lacZ reporter gene driven by an FC-specific enhancer (mib2-FCenhancer) is normal in pnt null mutant embryos (Fig.…”
Section: Visceral Founder Cell Specification Is Independent Of the Etmentioning
confidence: 91%